Therapeutic effect of CD137 immunomodulation in lymphoma and its enhancement by T(reg) depletion - Houot, Roch (American Society of Hematology, 2009)
Despite the success of passive immunotherapy with monoclonal antibodies (mAbs), many lymphoma patients eventually relapse. Induction of an adaptive immune response may elicit active and long-lasting antitumor immunity, thereby preventing or delaying recurrence. Immunomodulating mAbs directed against immune cell targets can be used to enhance the immune response to achieve efficient antitumor immunity. Anti-CD137 agonistic mAb has demonstrated antitumor efficacy in various tumor models and has now entered clinical trials for the treatment of solid tumors. Here, we investigate the therapeutic potential of anti-CD137 mAb in lymphoma. We found that human primary lymphoma tumors are infiltrated with CD137(+) T cells. We therefore hypothesized that lymphoma would be susceptible to treatment with anti-CD137 agonistic mAb. Using a mouse model, we demonstrate that anti-CD137 therapy has potent antilymphoma activity in vivo. The antitumor effect of anti-CD137 therapy was mediated by both natural killer (NK) and CD8 T cells and induced long-lasting immunity. Moreover, the antitumor activity of anti-CD137 mAb could be further enhanced by depletion of regulatory T cell (T(regs)). These results support the evaluation of anti-CD137 therapy in clinical trials for patients with lymphoma.